"Efficacy of Deltamethrin Impregnated Bednets for Control of Malaria in Dehdasht, Kohgiloyeh & Buyer Ahmad province, Iran, 1997-1998" - Rassi Y; Kamali F; Abai MR; MousaKazemi SH; Vatandoost H (Tehran University of Medical Sciences, 2002)
An Interventional field trial study was carried out in the Dehdahst area, Kohgiloyeh & Buyer Ahmad province, Iran, during 1997-1998. Efficacy of deltamethrin-impregnated bednet at target dosage of 25 a.i. mg/m2 and the incidence of malaria were compared in treated and untreated villages. In this area Anopheles superpictus is the dominant species and the activity of the species occurs in one peak, in August. Regarding to malaria incidence, the results showed a high reduction of Annual Parasite Incidence from 51.2 to zero in treated villages. Bioassay tests on impregnated bednet showed 100% mortality after 110 days and decreased to 97% after 120 days. Due to the exophilic and exophagic habit of vectors in treated areas, it could be concluded that the use of deltamethrin impregnated bed net could reduce the malaria incidence.